Study of Socio – Personal Profile and Awareness of Rural Women Regarding ICDS Activities in the Faizabad District of U.P - Garima Tiwari , P. Singh; Pinaki Roy (Indian Journal of Extension Education, 2017)
The study was conducted in Milkipur block of Faizabad district by interviewing a total of 100 respondents who were selected through proportionate random sampling technique. The study depicted that the highest number of respondents (59%) were found in the age category of 22 to 32 years belonging to joint families (62%) and having 5 to 8 members in their families (54%). The scheduled caste respondents were more in comparison to other categories of caste. The scientific orientation was observed of low level while value orientations and risk were observed of medium level. The contact of respondents with Auxiliary Nurse Midwife among formal sources, family members among informal sources and radio was observed important among mass media. Agriculture was observed as main family occupation of the respondents (55%) having annual income of upto Rs. 40000 (40%). An overwhelming majority of the respondents were found using cell phone as their main source of communication.